A Comprehensive Analysis of Barga Folk Songs: Morphological Structure, Socio-Cultural Functions, and Thematic Taxonomy - Ga, BiLa (International Journal of Literature and Arts Studies, 2026)
The song tradition of the Barga people holds an important place in Mongolian musical heritage. This article examines the musical characteristics of Barga folk songs, their linguistic and melodic features, socio-cultural functions, and main thematic classifications, highlighting their role in shaping ethnic customs and worldview. Barga folk songs are generally classified into two main musical forms: long songs (urtiin duu) and short songs (bogino duu). Barga long songs are distinguished by expansive spatial imagery, broad breath organization, and a wide melodic range, while short songs are more practical in use, with clear rhythmic structures closely tied to daily life. Furthermore, various thematic categories-such as praise songs, homesickness songs, love songs, wedding songs, military songs, and lullabies-express the deep cultural layers of Barga society. This study provides a systematic analysis of these songs from both musical structural and thematic-content perspectives to elucidate their significance within the broader framework of ethnic cultural heritage. The findings suggest that Barga folk songs constitute a unique and invaluable component of Mongolian ethnomusicology, serving as critical primary material for future scholarly research.